Features of the intestinal microbiota functional status in early-aged children with rotavirus infection - Vorobiova, N.; Usachova, O. (Journal of Education, Health and Sport, 2021)
The aim is to assess the intestinal microflora functional and structural disorders in early-aged children in the dynamics of rotavirus infection by studying intestinal metabolites in faeces – short-chain fatty acids (SCFA). Materials and methods. The study included 60 breastfed children aged 1-24 months with rotavirus infection (the study group) and 30 healthy children, representative by age and sex (the comparison group). Determination of SCFA (acetate, propionate, butyrate) in faeces was carried out in all children of the study group three times in the dynamics of the disease (on the 3rd, 5th and 10th day) and in healthy children once. Results. The total concentration of SCFA in children with rotavirus infection was 3 and 2.2 times lower than in healthy children in the acute period of the disease (p<0.01 on the 3rd and 5th day, respectively), increasing on the 10th day (p<0.05), however, not reaching the normal level (p<0.01). The decrease in the total pool of SCFA occurred due to all volatile acids (C2, C3, C4), the concentrations of which were lower than in healthy children (p<0.01). Violation of the volatile acids ratio in their general pool was observed from the first days of rotavirus gastroenteritis in the form of an increase in the C2 relative concentration (p˂0.05) and a decrease in C3 and C4 profiles (p˂0.05). Correspondingly, a decrease in anaerobic index was noted. It was equal to 0.04 [0.01; 0.11] on the 3rd and 5th day of the disease, constituting only 1/5 of the healthy children values (p˂0,01), increasing on the 10th day to 0,09 [0,02; 0.17], however, remaining twice as lower than in children of the comparison group (p˂0,01). Conclusions. There is a violation of the intestinal microflora functional condition in early-aged children from the first days of rotavirus infection, which is expressed by depletion of the total pool of SCFA and concentrations of each of them, as well as structural disorders of intestinal microbiocinosis in the form of reducing its anaerobiosis. These changes are most pronounced during the first five days of rotavirus gastroenteritis and last up to 10th day of illness.